Prevalence of Osteoporosis and Sarcopenia in Middle-Aged Subjects with Low Back Pain - Narayan, Shamrendra; Pratap, Rishabh; Raj, Gaurav; Chauhan, Abhishek; Kumar, Tushant; Singh, Neha; Singh, Ajai Kumar; Gupta, Nikhil (Indian Journal of Radiology and Imaging, 2024)
Objective The genesis of both osteoporosis and sarcopenia is multifactorial, complicated, and interrelated. The present study has been undertaken to analyze the prevalence of low bone mineral density (BMD) and the pattern of imaging markers of sarcopenia (paraspinal skeletal muscle area [SMA] and skeletal muscle index [SMI] with respect to clinicodemographic profile in middle-aged patients (30–45 years) undergoing evaluation for low back pain (LBP).Materials and Methods Magnetic resonance imaging (MRI) of the lumbosacral spine and/or sacroiliac joints was done on 3T MRI. BMD of the lumbar spine (L1 to L4) was assessed using a dual-energy X-ray absorptiometry scan. SMA was calculated by measuring the cross-sectional area of paraspinal muscles (bilateral psoas, erector spinae, and multifidus), and SMI was calculated by dividing SMA by height2.Results The prevalence of osteoporosis was 12.1% in patients of age 30 to 45 years presenting with LBP. Both osteoporosis and paraspinal muscle mass were statistically associated with the duration of symptoms (p-value <0.05). No statistically significant difference was observed in different MRI findings, that is, normal, inflammatory, infective, and degenerative etiology.Conclusion Low BMD and loss of muscle mass in cases with LBP are more related to duration of disease rather than etiology or gender in middle-aged subjects. Early intervention to manage LBP may prevent progression to osteoporosis and sarcopenia in young adults.
Keywords: low back pain; bone mineral density; osteoporosis; sarcopenia; skeletal muscle area; skeletal muscle index